Pemanfaatan Virtual Tour Museum Wajakensis Sebagai Sumber Belajar untuk Meningkatkan Pemahaman Siswa pada Pelajaran Sejarah Kelas X SMAN 1 Kauman Tulungagung (International Forum of Researchers and Lecturers, 2025)
This research is motivated by the challenges in history learning which tend to be conventional and less interesting so that it has an impact on students' low understanding of history material. The use of digital technology through a virtual tour of the museum is an innovative alternative to present a more interactive and contextual learning experience. Wajakensis Museum as a regional museum with a collection of historical artifacts in Tulungagung has great potential as a learning resource rich in historical and cultural values. The purpose of this study was to determine the effectiveness of utilizing the virtual tour of the Wajakensis Museum in improving students' understanding in history learning for class X SMAN 1 Kauman Tulungagung. The method used is descriptive qualitative with data collection through observation, interviews, and documentation. The results of the study indicate that the Wajakensis Museum virtual tour is effective in improving students' understanding of historical material by providing a more interesting, visual, and interactive learning experience. In addition, the use of virtual tours also increases student enthusiasm and participation during the learning process. Teachers and students stated that this media provides ease and efficiency of learning, especially in conditions of limited access to physical museums. The implications of this study indicate that the integration of technology in history learning can be a solution to improve the quality of history education and significantly enrich students' learning experiences.